The importance of angle kappa evaluation for implantation of diffractive multifocal intra-ocular lenses using pseudophakic eye model - Karhanová, Marta; Pluháček, František; Mlčák, Petr; Vláčil, Ondřej; Šín, Martin; Marešová, Klára (Acta ophthalmologica, 2015)
PURPOSE: To determine the critical value of the angle kappa in connection with a higher risk of photic phenomena for the AcrySof ReSTOR and Tecnis multifocal intra-ocular lens (MIOL) on a standardized pseudophakic eye model. To analyse the impact of biometric value changes on the critical angle kappa. METHODS: Geometrical optic rules applied to a suitable optical model of the pseudophakic eye were used to calculate the critical value of the angle kappa for the Tecnis and three types of the AcrySof ReSTOR MIOLs. The angle kappa was defined as critical if the incident ray passed through the first ring's edge area. The influence of different positive optical corneal power (K), effective lens position (ELP) and axial length (AL) on the critical angle kappa (κc) was investigated. The dependence of κc on one of the parameters was studied for standardized values of the remaining parameters. RESULTS: The highest value of the critical angle kappa was evaluated for the Tecnis MIOL. The increase in ELP and K caused an increase in κc under the given conditions. On the contrary, an increase in AL led to lower values of κc. CONCLUSION: We demonstrated the dependence of the critical angle kappa on the central part of the MIOL and on biometric parameters of the eye, especially on the effective lens position. According to these results, we conclude that shallow anterior chamber depth in connection with a higher angle kappa is an important risk factor for pronounced photic phenomena after implantation of a diffractive MIOL.
Keywords: optika a fotonika; photic phenomena; teoretické modely; nitrooční čočky; effective lens position; pupila; Optics and Photonics; rohovka; multifocal intra-ocular lens; Cornea; lidé; Lenses, Intraocular; axiální délka oka; Pupil; anterior chamber depth; pseudofakie; Pseudophakia; Lens Implantation, Intraocular; implantace nitrooční čočky; Models, Theoretical; angle kappa; Axial Length, Eye; Humans